The Impact of Creative Marketing on the Competitive Advantage of ServiceEnterprises: Applied to the Islamic Insurance Company (Khartoum State) in the period (2010-2020) - Mouhamed ali, TahirAhmed; Moussa ahmed mouhamed, Nisrin (Milev Journal of Research and Studies, 2021)
The study aimed to find out the effect of creative marketing on the competitive advantage in service organizations. The study found many results, the most important of which are: The company relies on information technology in providing its services to clients, and the positive impact of creative marketing on competitive advantage. Evaluate its services after they are delivered to customers to gauge their satisfaction.